2021
DOI: 10.1016/j.ypmed.2021.106593
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle interventions to reduce sedentary behaviour in clinical populations: A systematic review and meta-analysis of different strategies and effects on cardiometabolic health

Abstract: Cardiometabolic comorbidities are highly prevalent in clinical populations, and have been associated (partly) with their sedentary lifestyle. Although lifestyle interventions targeting sedentary behaviour (SB) have been studied extensively in the general population, the effect of such strategies in clinical populations is not yet clear. Therefore, this systematic review and meta-analysis evaluated the effect of different lifestyle interventions on SB and cardiometabolic health in clinical populations.Randomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
36
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 82 publications
6
36
1
2
Order By: Relevance
“…Our findings confirmed our hypothesis, with a significant reduction in BMI, body weight, and waist circumference in patients receiving the experimental intervention. Our results also support the recent finding that people with SMI can achieve healthy lifestyle through the provision of behavioral programs [ 67 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings confirmed our hypothesis, with a significant reduction in BMI, body weight, and waist circumference in patients receiving the experimental intervention. Our results also support the recent finding that people with SMI can achieve healthy lifestyle through the provision of behavioral programs [ 67 ].…”
Section: Discussionsupporting
confidence: 90%
“…The interventions consisted of the use of technologies, social facilitation, motivational counselling and self-monitoring. 76 As LBP is a complex disorder, health education to reduce the prevalence or occurrence of LBP should be address the risk factors as much as possible including sedentary behavior.…”
Section: Discussionmentioning
confidence: 99%
“…19 In the meantime, a meta-analysis suggested that reducing sedentary behavior among clinical populations could improve cardiometabolic risk markers such as waist circumference, fat percentage, and glycemic control. 20 Moreover, we found that differences in age were associated with the different levels of sedentary time. Surprisingly and interestingly, our data showed that older adults have the least sedentary time than other age groups, which is contrary to our speculation and studies in other countries.…”
Section: Discussionmentioning
confidence: 75%
“… 19 In the meantime, a meta‐analysis suggested that reducing sedentary behavior among clinical populations could improve cardiometabolic risk markers such as waist circumference, fat percentage, and glycemic control. 20 …”
Section: Discussionmentioning
confidence: 99%